Speckle phenomenon in optical fiber and its applications in sensors - Lomer, Mauro (2012)
A highly structured light pattern is observed when a coherent light beam is propagated by a multimode optical fiber and projected onto a screen. This pattern consists of a large number of small patches of bright light (English: speckle) on an opaque background, caused by the intermodal interference phenomenon. The speckle pattern varies slowly due to environmental factors surrounding the optical fiber, but the total intensity remains almost constant and can be registered by a single CCD camera. Any external perturbation (temperature, vibration, pressure, voltage, ...) performed on the fiber affects the speckle pattern. An appropriate image processing can allow extracting the causes of the disturbance source and build a correlation signal and its application to the extent of physical, chemical or biological. Generation occur speckle phenomenon in multimode optical fibers with a source of coherent light. We describe the theoretical concepts that are present in the phenomenon, the optical setup and the experimental demonstration, as well as some applications that can result in sensors.